ANALISIS STATUS GIZI, KEBIASAAN MAKAN DAN AKTIVITAS FISIK PADA MAHASISWA KESEHATAN DENGAN PENDEKATAN MIX-METHOD - Lies Permana; Nurul Afiah; Riza Hayati Ifroh; Agus Wiranto (Husada Mahakam, 2020)
Nutritional intake for adolescents was needed to increase activity and creativity to developt human resources in future. The main causes of nutritional problems in adolescents was poor eating habits, consumtion of low food quality, and the application of sedentary life. The research purpose was to identify and explore the description of nutritional status, eating behavior, and physical activity of students at the Faculty of Public Health, Mulawarman University. The research used sequential explanatory of mixed method, eating behavior was measured by using a questionnaire and the intensity of physical activity was measured using (IPAQ-SF), nutritional status was based on BMI with a sample size of 116 respondents. In collecting qualitative data through FGD to 21 informants. Quantitative data analysis by descriptive and qualitative by content analysis. The results showed that 50.9% of respondent in malnutrition and overnutrition status, 30.2% of respondents in over BMI had consuming high-calorie drinks, 34.7% of respondents in over BMI had low physical activity and often left breakfast. The conclusion of this research was these students' lifestyle category was eating fastfood and also consuming high-calorie drinks which are currently in sales such as milk, coffee, boba drinks, and chocolate drinks with relatively low physical activity intensity.